PENGARUH INSTAGRAM TERHADAP KEPUTUSAN BERKUNJUNG DI DESA WISATA SERANG, KABUPATEN BLITAR (Studi Survey pada Followers @dewaserang) - Susanti, Aidha; Danu Winata, M.A., M.Si. (Han), Muhammad (The Commercium, 2025)
This research aims to determine the influence of Instagram (X) on the decision to visit (Y) Serang Tourism Village, Blitar Regency. The population in this study were Instagram followers @dewaserang with a sample of 332 people taken using the Slovin formula. The type of research used is quantitative with a positivistic paradigm to determine cause and effect relationships in a social phenomenon. The data analysis techniques used are the Spearman Rank Correlation Test, Quadratic Regression Equation Test and Coefficient of Determination Test. The research results show that the Instagram variable has a significant relationship with Visiting Decisions of 25.1% and there is a fairly strong correlation between the 2 variables.